STUDY OF POTENTIAL MELAYU VILLAGE AS A HERITAGE AREA IN SEMARANG - Nuzulia Anggita; Nany Yuliastuti (Department of Urban and Regional Planning, Diponegoro University, 2018)
The urban village is a settlement that was established in the early period of the formation city and is the embryo of Semarang. Melayu Village is a heritage area where the existing heritage assets is inseparable from the history of the past. The enviromental of Melayu Village is quality conditions suffered environmental degradation because the threat of catastrophic tidal flood, the level of residential density is high, and there are several old buildings that were damaged. Assets contained in this region shows the evolution of human life and settlements from time to time that are still functioning properly. The purpose of this study to assess the potential in Melayu Village as a heritage area. This study uses descriptive quantitative and spatial analysis. The results of this study indicate that RW IV and RW VII are potentially as a heritage district with a score of 2.4 that characterized by a socio-cultural conditions that their religious activities in the form of cultural activities. This is also supported by the discovery of artifacts buildings in RW VII that Layur Tower Mosque and Shrine Kam Hok Bio who survived and functioned until today. Based on the potential of Melayu Village already should be protected as a heritage area.